Spatial reference frame of attention in a large outdoor environment - Jiang, Yuhong V. (2014)
A central question about spatial attention is whether it is referenced relative to the external environment or to the viewer. This question has received great interest in recent psychological and neuroscience research, with many but not all, finding evidence for a viewer-centered representation. However, these previous findings were confined to computer-based tasks that involved stationary viewers. Because natural search behaviors differ from computer-based tasks in viewer mobility and spatial scale, it is important to understand how spatial attention is coded in the natural environment. To this end, we created an outdoor visual search task in which participants searched a large (690 square feet), concrete, outdoor space to report which side of a coin on the ground faced up. They began search in the middle of the space and were free to move around. Attentional cuing by statistical learning was examined by placing the coin in one quadrant of the search space on 50% of the trials. As in computer-based tasks participants learned and used these regularities to guide search. However, cuing could be referenced to either the environment or the viewer. The spatial reference frame of attention shows greater flexibility in the natural environment than previously found in the lab.